Diverse cell types establish a pathogenic immune environment in peripheral neuropathy - Julie Choi; Amy Strickland; Hui Qi Loo; Wendy Dong; Lilianne Barbar; A. Joseph Bloom; Yo Sasaki; Sheng Chih Jin; Aaron DiAntonio; Jeffrey Milbrandt (Journal of Neuroinflammation)
Abstract Neuroinflammation plays a complex and context-dependent role in many neurodegenerative diseases. We identified a key pathogenic function of macrophages in a mouse model of a rare human congenital neuropathy in which SARM1, the central executioner of axon degeneration, is activated by hypomorphic mutations in the axon survival factor NMNAT2. Macrophage depletion blocked and reversed neuropathic phenotypes in this sarmopathy model, revealing SARM1-dependent neuroimmune mechanisms as key drivers of disease pathogenesis. In this study, we investigated the impact of chronic subacute SARM1 activation on the peripheral nerve milieu using single cell/nucleus RNA-sequencing (sc/snRNA-seq). Our analyses reveal an expansion of immune cells (macrophages and T lymphocytes) and repair Schwann cells, as well as significant transcriptional alterations to a wide range of nerve-resident cell types. Notably, endoneurial fibroblasts show increased expression of chemokines (Ccl9, Cxcl5) and complement components (C3, C4b, C6) in response to chronic SARM1 activation, indicating enhanced immune cell recruitment and immune response regulation by non-immune nerve-resident cells. Analysis of CD45+ immune cells in sciatic nerves revealed an expansion of an Il1b+ macrophage subpopulation with increased expression of markers associated with phagocytosis and T cell activation/proliferation. We also found a significant increase in T cells in sarmopathic nerves. Remarkably, T cell depletion rescued motor phenotypes in the sarmopathy model. These findings delineate the significant changes chronic SARM1 activation induces in peripheral nerves and highlights the potential of immunomodulatory therapies for SARM1-dependent peripheral neurodegenerative disease.